STUDY OF THE SAMURAI DEDICATION IN 47 RONIN MOVIE SCRIPT - Bondan Eko Suratno (Universitas Aki, 2017)
The writer is interested in discussing the 47 Ronin movie script with the title “A Psychological Study of the Samurai Dedication in 47 Ronin Movie Script” because it contains not only unique culture of suicidal action but also the action is highly respected in Japan. Besides, it also contains dedication and loyalty of followers to their master. The thesis research is conducted through the research in library room, here he gets primary data in the form of script from the movie. The writer also uses opinions from some experts (secondary data) to support his analysis. In the discussion, the writer also talks about intrinsic and extrinsic elements. Mentioning intrinsic elements because a literary works contains elements that build it, like characters, theme, plot, setting and point of view. And extrinsic elements are elements that exist outside a literary work but it has correlation with intrinsic elements.In the analysis, the writer finds out that the Samurai members of Ako area cannot accept their master to be blamed when the master (Lord Asano) has conflict with Lord Kira of high rank official. The two must be judged guilty. Lord Asano must commit seppuku and be beheaded as ordered by Shogun; not Lord Kira. The unfair judgment has triggered Lord Asano followers to take revenge. There are 47 samurai or ronin who take the action, and successful. Consequently, they (as regulated) must commit seppuku too but with honor, not hanged like criminals; because the ronin demand justice. People of Japan also honor them as great dedication.Oishi saves his Samurai members from launching a stupid attack on Lord Kira and Shogun elite troops. He must restrain himself and his members to do it at other time. This means that he still keeps his logic. Therefore, he is an ego character in the story. Kai who is not genuinely Samurai is a superego character. Because of his sacrifice the 47 Ronin under the coordinator of Oishi are able to defeat Lord Kira followers. Kai helps to kill the monster who is hovering and killing samurai members in the forest. Kai also supports the ronin to get lethal weapon that is difficult to get. Kai also kills a powerful witch or beautiful magician who always supports Lord Kira. On the other hand, Lord Kira is fully driven by id because he wants to kill and trap Lord Asano to take over his land, his area. He also drives away Ako people from the village. He keeps a concubine to trick the opponent to be defeated.Keywords: id, ego, superego, psychological analysis